Assessment of Effect of Alummina Addition on the Refraractory Under Load (Rul) Property of Some Kaolin Clay Deposits in Nigeria - Mokwa, J. B.; Abdullahi, M.; Malomo, O. E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
The impact of alumina addition on the Refractory Under Load (RUL) of kaolin clay deposits in Nigeria have been investigated. The samples deposit were collected from different sites of Ikpeshi Akoko Edo (IKAE) of Edo State, Kasadi Village in Kebbi State (KVK), Alasan in Osun State (AOS) and Badeggi in Niger State and were used as the principal raw material in the sample preparation while ball clay was used as the binder. The kaolin and ball clay were mixed in suitable proportion of 70:30 ratio in the production of the fire clay bricks. Particle size distributions and Refractory under load (RUL) of the samples were determined. Through RUL tests, samples without alumina exhibited varying subsidence behaviours at different temperatures. Samples from Kasadi (KVK) and Alaasan (AOS) showed the greatest improvement at 10% and 15% alumina levels, with lower subsidence and higher peak temperatures. With 10% and 15% alumina additions, respectively, the Kasadi sample reached maximal thermal stability with subsidence temperatures of 1475°C and 1516°C. Excellent refractory properties were likewise demonstrated by the Alaasan sample, but with less early expansion. On the other hand, the Ikpeshi (IKAE) sample underwent more overall deformation, suggesting a lower level of long-term thermal resistance, even if it was initially able to endure high temperatures. Results suggest alumina content influences the thermal stability and performance of kaolin clay, important for firebrick production and industrial applications. Practical tests confirmed the suitability of produced refractory bricks for industrial use, demonstrating comparable performance to standard refractory fire clay.